But is it public administration? the place of voluntary sector management in the discipline - Cariño, Ledivina V. (Philippine Journal of Public Administration, 1997)
They must learn to lead, manage and govern. This is what the various organizations in the Philippine voluntary sector need to inculcate among themselves in order to carry out if not serve more effectively their respective missions and correspondingly, their own constituents. As we look more closely into the purpose and objectives of the different groups across the country engaged in more or less volunteer work, it is instructive to make a comparison among business administration (BA), public administration (PA) and voluntary sector management (VSM) with emphasis on their differences ranging from market vis-a-vis state operations, profit-orientedness or public service administration and last but not the least, fund generation and fiscal administration. Also, a point not to be overlooked is the publicness-privateness continuum in VSM, wherein it like all other organizations, has both public and private characteristics.